Thermo-economic analysis of flare gas recovery for power and clean water production using integrated concentrated solar power and direct oxy-fuel combustion - Laveet Kumar (11460088) (2025)
This study investigates a novel approach for sustainable power generation and water production by integrating a flare-powered direct oxy-combustion supercritical CO2 power cycle with concentrated solar power. The main objective is to reduce emissions from oil and gas operations while producing clean electricity and water from waste resources. Using validated thermodynamic and economic models, the proposed system's performance was assessed under various operational scenarios and flare gas compositions. Results show that the integrated system improves the cycle efficiency by 11 % and the overall energy efficiency by 26 % compared to conventional standalone systems. It also reduces fuel consumption by 33 % and generates up to 1.38 kg/s of clean water, providing dual benefits in regions facing both energy and water shortages. The thermo-economic analysis reveals a 11 % lower levelized cost of electricity for the integrated system, particularly when utilizing NaNO3/NaNO2/KNO2 (7/40/53 wt%) salt as the thermal energy storage. Unlike prior studies, this study introduces a system that operates without carbon emissions by using pure oxygen for combustion and enables practical integration with solar power without the need for large-scale energy storage. The proposed system offers a techno-economically viable solution for industrial decarbonization and resource recovery, addressing critical gaps in the existing literature. Other Information Published in: Energy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.energy.2025.138091